Cross-Cultural Identity and Self-Discovery in Raja Rao’s ‘The Serpent and the Rope’ - Sinha, Dr. Arpana (Journal of Advanced Research in English & Education; Vol 5 No 3 (2020): Journal of Advanced Research in English & Education, 2020)
‘The Serpent and the Rope’, Raja Rao’s magnum opus, serves as a profound exploration of cross-cultural identity and the arduous journey of self-discovery. Through the protagonist, Rama, an Indian Brahmin intellectual residing in Europe, the novel delves into the complex interplay between Eastern spirituality and Western materialism. Rama’s marriage to the French teacher Madeleine and his numerous encounters with European intellectuals and landscapes highlight the chasm between his Vedantic worldview and their rationalist, empirical perspectives. His struggle is not merely an external one of navigating different social customs but a deeply internal conflict between his cultural roots and his adopted intellectual environment.This article explores how Rao uses the themes of love, illusion (maya), and the quest for truth to dismantle conventional notions of identity. It argues that for Rama, and by extension for the novel’s philosophical core, true self-discovery lies not in a synthesis of East and West, but in transcending both to realise a universal, non-dualistic truth. The article posits that the “rope” of European rationalism and the “serpent” of Indian illusion are ultimately the same, and that enlightenment comes from recognising their illusory nature.